2013
DOI: 10.1371/journal.pone.0077703
|View full text |Cite
|
Sign up to set email alerts
|

A New Short Oligonucleotide-Based Strategy for the Precursor-Specific Regulation of microRNA Processing by Dicer

Abstract: The precise regulation of microRNA (miRNA) biogenesis seems to be critically important for the proper functioning of all eukaryotic organisms. Even small changes in the levels of specific miRNAs can initiate pathological processes, including carcinogenesis. Accordingly, there is a great need to develop effective methods for the regulation of miRNA biogenesis and activity. In this study, we focused on the final step of miRNA biogenesis; i.e., miRNA processing by Dicer. To test our hypothesis that RNA molecules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 51 publications
3
27
0
1
Order By: Relevance
“…3, demonstrated that hDicer efficiently bound ssRNAs longer than ~20-nt, while it did not form a complex with a 12-nt ssRNA, and binding of a 14-nt ssRNA was very inefficient. These results also confirmed our previous observations that 12-nt ssRNA oligonucleotides, designed to interact with apical and/or single-stranded regions of pre-miRNAs, do not interact with hDicer (Kurzynska-Kokorniak et al, 2013).…”
Section: Binding Between Hdicer and Single-stranded Rnas Of Differentsupporting
confidence: 92%
See 4 more Smart Citations
“…3, demonstrated that hDicer efficiently bound ssRNAs longer than ~20-nt, while it did not form a complex with a 12-nt ssRNA, and binding of a 14-nt ssRNA was very inefficient. These results also confirmed our previous observations that 12-nt ssRNA oligonucleotides, designed to interact with apical and/or single-stranded regions of pre-miRNAs, do not interact with hDicer (Kurzynska-Kokorniak et al, 2013).…”
Section: Binding Between Hdicer and Single-stranded Rnas Of Differentsupporting
confidence: 92%
“…Preparations of hDicer are also commercially available. Our previous studies focusing on the regulation of the hDicer cleavage activity by short RNA molecules were carried out with commercial enzymes (Tyczewska et al, 2011;Kurzynska-Kokorniak et al, 2013). While we found them appropriate for assays based on pre-miRNA cleavage reactions, they do not seem to be suitable for detailed RNA-binding studies.…”
Section: Influence Of the Homogeneity Of The Recombinant Human Dicer mentioning
confidence: 89%
See 3 more Smart Citations